A Social Learning Model of Antisocial Coaching Behavior - Kabiri, Saeed (International journal of offender therapy and comparative criminology, 2020)
Studies of antisocial behavior in sports are important, although most lack a theoretical framework. The current study examines the endorsement of antisocial behavior in a sample of coaches using social learning theory. This features a survey of 268 Head Coaches and Assistant Coaches in the Tehran Provincial League, Iran. Results indicate that differential association, differential reinforcement, definitions, and imitation have a significant impact on antisocial behavior, with differential association being the most influential construct. Higher education in coaches was associated with lower levels of antisocial behavior. This suggests that antisocial coaching behavior is learned in a similar manner to prosocial behaviors, and that desistance requires assessment of the learning process.